Treatment Considerations for Patient with amelogenesis imperfecta: a review - Chen, Chiung-Fen; Hu, Jan CC; Bresciani, Eduardo; Peters, Mathilde C; Estrella, Maria Regina P (Brazilian Dental Science, 2013)
Objectives: Amelogenesis imperfecta (AI) is a group of inherited disorders primary affecting the structural of enamel. Patients with AI experience poor esthetic excessive tooth sensitivity and compromised chewing function that dental treatments are frequently required at early age. This review describes the nonenamel implications, stage-specific management strategies and outcomes of selected restorative materials based on literature evidence.Keywords Amelogenesis imperfecta; Dental enamel, abnormalities; Dentistry, operative.